Measuring University Students' Adaptability: A Brief Scale to Improve Effective Learning Processes - Putra, Ade Herdian; Ardi, Zadrian; Berlian, Gebriella (Universitas Negeri Padang, 2025)
This study aims to develop a brief scale that can measure adaptation skills in learning among university students. Adaptation skills are essential for facing challenges in the dynamic educational environment. The developed scale consists of five items covering indicators such as the ability to cope with change, openness to new experiences, stress management, learning independence, and collaboration skills. The Adaptation Theory by Schunk and Zimmerman (2012) serves as the foundation for the development of this scale. Data were collected through questionnaires distributed to students across various study programs, and analysis was conducted to test the scale’s validity and reliability. Validity was assessed using confirmatory factor analysis with factor loadings, while reliability was measured using Cronbach's Alpha. The results show that this scale has good validity and reliability, making it suitable for evaluating students' adaptation skills. These findings are expected to provide insights for the development of educational programs that support the enhancement of students’ adaptation skills in their learning process.